Fakenews is much more than fake content - Cristea, Darie; Fîrțală, Valeriu (Technium Social Sciences Journal, 2023)
The goal of this article is simple. In the context in which there is more and more talk about the concept of fakenews, there are also efforts to instrumentalize and operationalize it. Rightly so, from media to commerce, from social networks to propaganda, the phenomenon is at the heart of the communication processes we use today, but also at the heart of the problems we face as societies. Unfortunately, fakenews is a much more subtle concept than people think and the big question is whether this phenomenon can be approached legally, without violating the right to opinion and free expression. Our article deals precisely with these subtleties of the concept and puts them in parallel with the normative basis that we now have as a reference. What can and cannot be done in this area ultimately depends on our ability to correctly understand the manifestations of what we call fakenews.